Qualitative study on the perceived enablers and barriers to interprofessional education in primary care in Singapore - Cia Sin Lee; Zhimin Poon; Jeremy Cong En He; Bandy Quiling Goh; Cindy Xin Yi Poh; Muthulakshimi Paulpandi; Ee Guan Tay; Jascha De Nooijer (BMC Primary Care)
Abstract Background There is a need to strengthen interprofessional collaborative practice (IPCP) through interprofessional education (IPE) to improve patient outcomes. To contextualise IPE in primary care, there is a need to understand the factors associated with IPE. This study aims to identify the perceived enablers and barriers of IPE, taking diabetes care as an example, among practising professionals, educators, and institution leaders in primary care. Methods A qualitative study was conducted in primary care clinics in Singapore. The maximum variation purposive sampling approach was employed and a total of 20 participants were recruited, comprising of 14 healthcare professionals (HCPs), 3 educators, and 3 leaders. Basic demographics data were collected followed by individual semi-structured interviews using a topic guide. Conceptual framework by D'amour and Oandasan was adopted as the underpinning framework to evaluate factors associated to micro (learners and educators), meso (instituitions) and macro (policy and professional bodies) level. Thematic analysis method was adopted for data analysis. Results Ten themes were identified in this study. For HCPs at the micro level, the themes illustrated interprofessional interactions influenced by learning and work environments, and receptiveness towards IPE shaped by HCPs' attitudes. Additionally, interprofessional collaboration was enhanced through increased interprofessional knowledgeability and overcoming interprofessional hierarchy, while effective communication was fostered by establishing trust, respect, and overcoming psychological barriers. For educators at the micro level, the key themes included the attitudes of educators and the importance of professional development, as well as curriculum development. At the meso level, institutions focused on themes such as resource allocation, system changes, and outcome measurements in the implementation of the IPE programme, along with leadership support for IPE. At the macro level, the emphases were on the roles of policymakers in funding and defining national strategy, as well as the roles of professional bodies in providing educational resources. Conclusions This study demonstrated the complexity and interrelation of the factors associated with IPE in primary care. A multi-pronged approach needs to be adopted to address all the barriers in the future implementation of the IPE model in primary care and to design an IPE curriculum that integrates well with clinical practice. Clinical Trial Number Not Applicable.